1977
DOI: 10.1128/jvi.21.1.347-357.1977
|View full text |Cite
|
Sign up to set email alerts
|

Proteins of hepatitis B surface antigen

Abstract: Purified 22-nm forms of hepatitis B surface antigen (HBsAg) representing the three major antigenic subtypes (adw, ayw, and adr) were analyzed for their constituent polypeptides by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. No consistent difference in either the number or relative distributions of the polypeptides was observed for the various subtypes. Seven polypeptides were designated as P-1 through P-7 in order of their decreasing mobilities. By comparison with protein standards, their molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

1977
1977
1986
1986

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Relationship among the major polypeptides of HBsAg subtypes (adw, ayw, and adr). SDS-PAGE of HBsAg subtypes adw, ayw, and adr revealed that each had a pair of major polypeptides with apparent molecular weights of 24,000 (P-24) and 28,000 (P-28) (data not shown), as previously described (18). Peptide maps of the P-24 of each subtype are shown in Fig.…”
Section: -22supporting
confidence: 81%
“…Relationship among the major polypeptides of HBsAg subtypes (adw, ayw, and adr). SDS-PAGE of HBsAg subtypes adw, ayw, and adr revealed that each had a pair of major polypeptides with apparent molecular weights of 24,000 (P-24) and 28,000 (P-28) (data not shown), as previously described (18). Peptide maps of the P-24 of each subtype are shown in Fig.…”
Section: -22supporting
confidence: 81%
“…(The pre-S protein sequences of GSHV and HBV show only 17% identity, and they differ in length by 44 amino acids as a result of internal deletions or additions.) (iii) Proteins larger than mature sAg, with shared peptides and immunological reactivity, have been found in hepadnavirus particles (4,14,23,25). The most prominent of these proteins has a molecular weight of ca.…”
mentioning
confidence: 99%
“…apparent molecular weights by 6,500. Based on previous estimates for the carbohydrate content of HBSAg (10) and the pattern of periodic acid-Schiff stain reaction in polyacrylamide gels (14), carbohydrate should comprise no more than 25% by weight of the P-2 molecule and would account for an overestimate in molecular weight of about 2,500 (12). Therefore, the P-1 and P-2 polypeptides actually differ in molecular weight by at least 4,000.…”
mentioning
confidence: 96%
“…The approximately 22-nm form of hepatitis B surface antigen (HBAg) consists of at least seven polypeptides of which P-1 (23,000 daltons) and P-2 (29,500 daltons) are the major components (3,13,14). A third polypeptide, P-6 (72,000 daltons), is observed as a major polypeptide in some preparations.…”
mentioning
confidence: 99%
See 1 more Smart Citation